The Boma: ILRI says farewell to Director General Jimmy Smith - International Livestock Research Institute (International Livestock Research Institute, 2022)
Every director general knows, at the time they are appointed, exactly when they're supposed to leave because their appointment letter tells them so, says Jimmy Smith, who has been the director general of the International Livestock Research Institute (ILRI) for the past 11 years. But "I didn't realise how difficult it would be to say goodbye to ILRI and the staff."